Naẓarīyah “Martabat Tujuh” fī Niẓam al-Mamlakah al-Buṭunīyah - Yunus, Abdurrahim (Studia Islamika, 1995)
"Dignity Seven" is not unfamiliar to the people of Buton. Relics of the old manuscripts show that the teachings of tasawwuf sultanate is spread in sudan long Buton. At the very least, since the 17th century, when Sultan Dayanu Ihsanuddin reign, the theory of "the dignity of the seven" was becoming known. Even so, there is no written record of this period; The oldest manuscript only came from the mid-19th century, when the imperial power was at Sultan Muhammad Idrus Kaimuddin (1824-1851).DOI: 10.15408/sdi.v2i1.843